Edukasi Pendewasaan Usia Perkawinan (PUP) bagi Siswa/Siswi Tingkat Menengah Atas - Baiq Dewi Kamariani; Asrifia Ridwan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Early marriage is now a serious problem not only at the national level but at the regional/regency/city level. Early marriage is one of the strategic youth issues that must be resolved immediately. One of the government's strategies in reducing the number of early marriages is the Marriage Age Maturity Program (PUP). Through this program, every government, academician, community and early marriage eradication group collaborate in the success of the program. The educational activity on Marriage Age Maturity (PUP) which was carried out at MA NW Bagik Payung Selatan went smoothly, it's just that there were a number of problems, namely in terms of the characteristics and mindset of students who still underestimate the dangers of early marriage. In addition, the environment where they live is also supportive when they do underage marriages. This service uses an interactive approach with the FGD method. Efforts to reduce the number of early marriages at MA NW Bagik Payung Selatan must be supported by the school and parents, not only the government's task so that the Marriage Age Maturity Program (PUP) can produce optimal results